Synthesis and Characterization of Colistin-Functionalized Silica Materials for Rapid Capture of Bacteria in Water - Jingli Qiu; Jianli Li; Xiaoxi Du; Tong Zhou; Bingbing Xie; Limin He (Molecules, 2022)
In this study, a new colistin-functionalized silica gel material (SiO2@NH2@COOH@CST) was synthesized after carboxylation on the surface of amino-modified silica. The main factors affecting the adsorptive properties of the material, such as the types of linkers, the linking methods, the reaction buffers and the particle sizes of carriers, were systematically investigated. The SiO2@NH2@COOH@CST was characterized by means of electron microscopy, Fourier-transform infrared spectroscopy, zeta potential measurements, etc. We demonstrated that the sorbent showed good adsorption of Gram-negative bacteria. The adsorption efficiency of E. coli on SiO2@NH2@COOH@CST was 5.2 × 1011 CFU/g, which was 3.5 times higher than that on SiO2@NH2@COOH, suggesting that electrostatic interactions between SiO2@NH2@COOH@CST and E. coli played a key role. The adsorption was quick, and was reached in 5 min. Both pseudo-first-order and pseudo-second-order kinetic models fit well with the dynamic adsorption process of SiO2@NH2@COOH@CST, indicating that physical adsorption and chemisorption might occur simultaneously during the adsorption process. SiO2@NH2@COOH@CST was successfully applied for the rapid capture of bacteria from water. The synthesized material could be used as a potential means of bacterial isolation and detection.